Subjekt in objekt v odnosu med medicinsko sestro in bolnikom - Ščavničar, Ema (Obzornik zdravstvene nege, 2002)
The article presents the relationship between patient/client and nurse. The autthor stresses the role of a subject of both partners and stresses the importance of nursing care in conceptual frame within which patient occupies the centre, while nurse supports his active role within his capacities. The importance of supervision is also stressed which can be of great help to the nurse, as well as routine reflection upon work and relationship.
Keywords: bolniki; Filozofija zdravstvene nege; Medicinska sestra-bolnik, odnosi; medicinske sestre; Nurse-patient relations; Philosophy, nursing; zdravstvena nega